Helmeted Muskox (Bootherium bombifrons) from Near Fort Saskatchewan, Alberta: Dating Evidence for Redeposition in Late Pleistocene Alluvium - Hills, Leonard; Wilson, Michael (Géographie physique et Quaternaire, 2003)
AbstractSuperimposition and intersection of preglacial and postglacial valley systems on the Canadian plains indicates that some of the recovered Quaternary vertebrate fossils may be redeposited. To test this proposition, an accelerator mass spectrometer (AMS) date was obtained on bone from a previously described helmeted muskox skull from near Fort Saskatchewan, Alberta. The specimen, identified as Bootherium bombifrons = Symbos cavifrons was previously thought to be Late Pleistocene (postglacial) in age but showed evidence of transport. A date of 30 570 ± 250 14C yrs BP indicates that it is of Middle Wisconsinan (pre-Last Glacial Maximum) age and therefore was ultimately derived from the Empress Formation (Saskatchewan Gravels and Sands) in the Edmonton area. Other vertebrate fossils must be assessed carefully in this light and direct dating is recommended wherever possible to facilitate both stratigraphic and paleontological studies.